2021
DOI: 10.1002/iid3.465
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting USP14 ameliorates inflammatory responses in trophoblast cells by suppressing MAPK/NF‐κB signaling

Abstract: Background Preeclampsia can cause severe consequences for pregnant women and infants, and developing effective medicine or methods to prevent or treat patients with preeclampsia is urgently needed. Ubiquitin‐specific protease 14 (USP14) has emerged as a critical regulator in the development of human cancers and neurodegenerative diseases. However, its role in preeclampsia remains elusive. Methods The expression of USP14 in placental tissues from healthy donors and preeclampsia patients were determined by quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…5A-B). According to the literature, Adrenomedullin2 (ADM2), activating transcription factor 6 (ATF6), CANX, Endoplasmic reticulum degradation-enhancing α-mannosidase-like protein 1 (EDEM1), Mesencephalic astrocyte-derived neurotrophic factor (MANF), and Ubiquitin-speci c protease 14 (USP14) are closely linked with PE or Aβ [15][16][17][18][19][20], which further validated their expression levels in our study. Consistently, they were signi cantly differentially expressed in placental tissues of NP and PE, as well as in HTR-8/SVneo cells induced with or without TM (Fig.…”
Section: Identi Cation Of Degs Associated With the Upr In Pe And Thei...supporting
confidence: 79%
“…5A-B). According to the literature, Adrenomedullin2 (ADM2), activating transcription factor 6 (ATF6), CANX, Endoplasmic reticulum degradation-enhancing α-mannosidase-like protein 1 (EDEM1), Mesencephalic astrocyte-derived neurotrophic factor (MANF), and Ubiquitin-speci c protease 14 (USP14) are closely linked with PE or Aβ [15][16][17][18][19][20], which further validated their expression levels in our study. Consistently, they were signi cantly differentially expressed in placental tissues of NP and PE, as well as in HTR-8/SVneo cells induced with or without TM (Fig.…”
Section: Identi Cation Of Degs Associated With the Upr In Pe And Thei...supporting
confidence: 79%
“…USP14, an important member of the USP protein family, participates in a variety of cellular signaling pathways, such as Wnt/β catenin and MAPK/NF-κB [ 34 , 35 ]. Previous studies have revealed that the biological functions of USP14 are regulated by its proteasome and post-modifications [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, b-AP15 not only regulates UCHL5, but also acts on USP14. It has been reported that USP14 may up-regulate the production of pro-inflammatory cytokines through the NF-κB pathway 51 , and USP14 may enhance the dedifferentiation effect of IL-1β on chondrocytes 52 . Recently, an inhibitor of UCHL5 was designed by possibly blocking its deubiquitinating function, and contributed to the accumulation of polyubiquitinated substrates 53 .…”
Section: Discussionmentioning
confidence: 99%